Embodied experiences of injured endurance runners: a qualitative meta-synthesis - Leanne Hall; Paul Rhodes; Anthony Papathomas (2021)
A meta-synthesis was conducted to explore the experiences of ultra-runners who had sustained a running related injury. We identified 10 narrative studies which were synthesised thematically before being re-organised within an Embodiment framework producing 5 taxonomies; The Disciplined Body, Embodied Distress, Corporeal Running Identity, Intersubjectivity of pain and Embodied Coping. Ultra-running is a body centred activity exemplifying Merleau-Ponty’s embodiment. These runners develop a heightened kinaesthetic awareness and embodied sense of space developed through many hours of ‘burning in’ movement pathways. Running as a habituated and pre-reflective action means that when experiencing injury, the entire world of the ultra-runner is disrupted, calling into question their corporeal identity. Ultra-runners who experience pain or injury may have the opportunity to resist dominant pain narratives by adopting an embodied approach to healing. This meta-synthesis has implications for further research, examining the embodied meaning injured ultra-runners make from injury and how this impacts their experiences of their bodies.